KETEPATAN DALAM PENANGANAN PEMERIKSAAN PASIEN ASTIGMAT DI SUPER OPTICAL PADANG - Rina Novalinda (Ensiklopedia of Journal, 2020)
This scientific paper discusses the Accuracy in Handling Astigmat Patient Examinations in Super Optik. Al Padang. This study aims to: (1) Knowing the examination procedure for astigmatism refraction disorder patients. (2) appropriate treatment for sufferers of astigmatism refraction. This type of research is quantitative descriptive. The population in this study were all patients suffering from astigmatism refraction abnormalities. Sampling in this study is the total sampling technique. Data was collected through a questionnaire, then the data were discussed in accordance with the theories proposed in the literature review. The results of the study proved that respondents did not know the procedure for astigmatism refraction examination abnormalities, further than 30 respondents there were 9 respondents or 30% knew the procedure for astigmatism refraction examination abnormalities and 21 respondents or 70% did not know the procedure for examining astigmatism refraction abnormalities, and 19 respondents or 63.3 % felt the right treatment for sufferers of astigmatism refraction and as many as 11 respondents or 36.7% did not feel the right treatment for sufferers of astigmatism refraction.